Impact of elevated UVB radiation on marine biota: a meta‐analysis. Issue 1 (25th July 2012) - Llabrés, Moira; Agustí, Susana; Fernández, Miriam; Canepa, Antonio; Maurin, Felipe; Vidal, Francisco; Duarte, Carlos M.; Rex, Michael
Abstract Aim The emission of chlorofluorocarbon compounds eroded the ozone layer, raising incident ultraviolet B radiation to levels that affect biota. However, the role of UVB radiation (280–315 nm), which remains elevated to date, as a possible driver of the widespread global deterioration of marine ecosystems has not yet been fully quantified. In this paper we assess the magnitude of the impacts of elevated UVB radiation and evaluate the relative sensitivity to UVB across marine taxa and processes. Location The analyses presented are based on 1784 experimental assessments of the impacts of UVB performed with natural radiation and organisms from different geographical areas, as well as with artificial radiation and cultured organisms at many laboratories around the world. Methods First we compiled the published literature concerning experimental evaluation of the impacts of UVB on marine biota. Then a meta‐analysis was conducted with the data set obtained to evaluate the responses of marine organisms and processes to enhanced and reduced UVB levels. Results Increased UVB radiation leads to a sharp increase in mortality rates across marine taxa, with protists, corals, crustaceans and fish eggs and larvae being most sensitive. A general relationship between relative changes in UVB doses and mortality rates was developed. This relationship can help assess the effects of changes in incident UVB radiation (past, present or future) on marine organisms. Main conclusions This meta‐analysis demonstrates that mortality rates of marine biota increase rapidly in response to elevated UVB radiation. The enhanced mortality rates associated with currently elevated UVB levels may represent a major threat to marine biota, possibly underlying recent widespread declines in the abundance of marine organisms ranging from corals to fish and krill.